2016
DOI: 10.1016/j.neubiorev.2015.09.009
|View full text |Cite
|
Sign up to set email alerts
|

Where does brain neural activation in aesthetic responses to visual art occur? Meta-analytic evidence from neuroimaging studies

Abstract: Here we aimed at finding the neural correlates of the general aspect of visual aesthetic experience (VAE) and those more strictly correlated with the content of the artworks. We applied a general activation likelihood estimation (ALE) meta-analysis to 47 fMRI experiments described in 14 published studies. We also performed four separate ALE analyses in order to identify the neural substrates of reactions to specific categories of artworks, namely portraits, representation of real-world-visual-scenes, abstract … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
88
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(93 citation statements)
references
References 50 publications
2
88
2
1
Order By: Relevance
“…Importantly, the outcome of the current study may have direct consequences for linking cognitive models of esthetic experience with current neuroimaging data (Cela-Conde et al, 2013; Chatterjee and Vartanian, 2014; Leder et al, 2015). In the last decade, neuroimaging studies on the appreciation of visual art have suggested that, rather than a single brain area, there is a complex neural system that underlies esthetic experiences (Nadal, 2013; Cela-Conde and Ayala, 2014; Vartanian and Skov, 2014; Boccia et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…Importantly, the outcome of the current study may have direct consequences for linking cognitive models of esthetic experience with current neuroimaging data (Cela-Conde et al, 2013; Chatterjee and Vartanian, 2014; Leder et al, 2015). In the last decade, neuroimaging studies on the appreciation of visual art have suggested that, rather than a single brain area, there is a complex neural system that underlies esthetic experiences (Nadal, 2013; Cela-Conde and Ayala, 2014; Vartanian and Skov, 2014; Boccia et al, 2016). …”
Section: Introductionmentioning
confidence: 99%
“…If sensory immersion and arousal play a role in aesthetic perception, then the expected outcome is precisely that we should attest a positive correlation between aesthetic preference and the activation of the various brain areas involved in the processing of the stimuli. This prediction was also confirmed in a meta-analysis, likewise reporting an association between visual aesthetic experience and a wide-spread rather than localized brain activation (Boccia et al, 2016). In the case of music, the prediction is that the removal of relevant features, whether spatial, emotional, or spectral, should lead into a marked decrease both in the brain activation and in the aesthetic judgment.…”
Section: Sensory Aesthetics As Immersion and Arousalmentioning
confidence: 59%
“…Finally, emotional systems mainly located in the frontal cortex and partially belonging to the so-called Default Mode Network (DMN; [5]) may be involved in VAE, especially when individuals explicitly focus on emotions raised from watching works of arts, such as horror, disgust, and so on [6]. In the past decade, several studies assessing the neural underpinnings of aesthetic experience, especially by using functional magnetic resonance imaging (fMRI) in healthy participants ([7,8] for review and meta-analysis), found evidence that strongly supports this model of VAE. Indeed, VAE has been found to rely on a wide network of brain areas consisting of sensory systems [6] and attributional areas of the ventral visual stream [6,7,9], differently engaged as a function of the content of the artwork [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the past decade, several studies assessing the neural underpinnings of aesthetic experience, especially by using functional magnetic resonance imaging (fMRI) in healthy participants ([7,8] for review and meta-analysis), found evidence that strongly supports this model of VAE. Indeed, VAE has been found to rely on a wide network of brain areas consisting of sensory systems [6] and attributional areas of the ventral visual stream [6,7,9], differently engaged as a function of the content of the artwork [7]. Within this network, aesthetic preference (e.g., positive or negative aesthetic judgment or the degree of experiences attractiveness) is also processed [10,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation